Effect of Processing Conditions, Additives and Starch Substitution on the Quality of Starch Noodle - Kusnandar, Feri (1998)
Starch noodle is a popular noodle in Asian countries, including Malaysia. In China and Thailand, the noodle is usually made from mungbean starch but in Malaysia it is made from a mixture of 95% potato starch and 5% mungbean starch. Although uncooked potato starch noodle has similar characteristics with noodle made from 100% mungbean starch, it becomes sticky, experiences high cooking loss and does not retain its shape well when cooked in water. In this project, methods for improving the quality of potato starch noodle were studied. It was found that both dough moisture content and freezing temperature of wet noodles significantly affect transparency, dimension, cutting stress, cooking loss and swelling index of noodles. They did not affect noodle stickiness. Based on the results obtained using Response Surface Methodology (RSM), the dough moisture content and freezing temperature of wet noodles suitable for potato starch noodle processing were 51.5 to 54.3% and -5 to -7°C, respectively. The strength, dimensions and transparency of the uncooked noodle produced were comparable to that of commercial potato starch noodle and mungbean noodle. Its cooking loss and swelling index, however, were lower than that of commercial potato starch noodle but higher than that of mungbean noodle. Addition of a mixture of potassium alum (0.64-0.86%) and alginic acid (0.30-0.46%) in the dough formula reduced cooking loss, swelling index and stickiness of cooked noodle to that comparable to those of mungbean noodle. In addition, they improved dough consistency, strength of uncooked noodle and firmness of cooked noodle and resulted in cooked noodle with acceptable dimension, transparency, elasticity and taste. The effects of these additives on the noodle, in particular on cooked noodle mimicked their effects on potato starch paste. Potassium alum and alginic acid, when added separately or together into a starch slurry, delayed starch gelatinization and viscosity breakdown, decreased hot paste viscosity and set-back, and reduced swelling power and solubility of potato starch paste. Substitution of potato starch up to 17% with tapioca starch phosphate, up to 35% with MTS283 (commercial tapioca starch phosphate) or up to 35% with sago starch phosphate improved the quality of potato starch noodle. The noodle produced is less brittle when uncooked, and is more elastic, firmer and experience lower cooking loss and less swelling when cooked. Out of the three types of noodles made using modified starches, starch noodle containing MTS283 was the most preferred. Substitution of potato starch with native tapioca or sago starch up to 17% is also possible. The noodle prepared using modified starches, however, is more transparent and less brittle when uncooked, and is more elastic, firmer and more acceptable in terms of taste when cooked.